Recent advances in degradable synthetic polymers for biomedical applications ‐ Beyond polyesters. (June 2022) - Dirauf, Michael; Muljajew, Irina; Weber, Christine; Schubert, Ulrich S.
Abstract: Polyesters have been studied intensely over the last few decades and proved to be suitable for a wide range of applications. Despite all benefits, drawbacks such as e.g. the acidification of the microenvironment during degradation, represent ongoing issues. Therefore, the necessity of developing alternative materials in e.g. drug delivery systems represents an emerging field in polymer science. In that regard, this review covers the latest developments of (bio)degradable synthetic polymers beyond polyesters. In spite of seemingly different on first glance, poly(ester amide)s, polyphosphoesters as well as polyacetals have recently experienced a boost with respect to the development of new synthetic routes that enable access to more tailored materials. The successful synthesis and characterization of the new materials represent fundamental premises for the understanding of structure-property relationships which, in turn, form the basis for the development of reasonable tailored pharmapolymers. The review hence scrutinizes the recent synthetic developments of these polymer classes throughout the last 10 years, putting them into the context of applications that have arisen for less novel materials. Graphical abstract: Image, graphical abstract